واقع الأداء الوظيفي لمديرات رياض الأطفال من وجهة نظر معلمات الرياض في محافظة اللاذقية - الجندي, نزيه; علي, وفيقة (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدف البحث إلى التعرف إلى مستوى الأداء الوظيفي لمديرات رياض الأطفال في محافظة اللاذقية من وجهة نظر معلمات الرياض، وكذلك التعرف إلى الفروق في مستوى أدائهن تبعاً للمتغيرات الآتية (عدد سنوات الخبرة، المستوى العلمي، الدورات التدريبية). استخدم البحث المنهج الوصفي التحليلي، واشتملت العينة على (78) معلمة من معلمات رياض أطفال محافظة اللاذقية للعام الدراسي 2011/2012. ولتحقيق هدف البحث صممت استبانة مكونة من خمسة مجالات كالآتي (إدارة العاملين في الروضة، إدارة الروضة مالياً ومادياً، الاتصال بأولياء الأمور والمجتمع المحلي، تنفيذ منهاج الروضة، العناية بالأطفال)، والتي تمثل الأداء الوظيفي لمديرات الرياض. أظهرت النتائج أن مستوى الأداء الوظيفي لمديرات الرياض جاء بدرجة متوسطة، وبينت النتائج وجود فروق دالة وجوهرية في مستوى أدائهن تبعاً للمستوى التعليمي، لصالح المستوى التعليمي الأعلى، كما وجدت فروق دالة تبعاً لمتغير الخبرة التي تمتلكها مديرات الرياض لصالح ذوي الخبرة الأعلى، في حين بينت النتائج أن المديرات اللواتي خضعن لدورات تدريبية جاء أدائهن أعلى من المديرات اللواتي لم يخضعن لدورات تدريبية، قدم الباحث مقترحات لتحسين مستوى الأداء الوظيفي لمديرات الرياض، أهمها زيادة عدد الدورات التدريبية لمديرات رياض الأطفال، ووضع أسس علمية لاختيار مديرات رياض الأطفال من ذوي الكفاءات والخبرة. The purpose of this research is to recognize the level of Functional Performance of the Kindergarten Principals in the District of Lattakia From the Kindergarten Teachers' Point of View and to recognize the difference in their performance levels according to the following variables (years of experience, scientific level, training courses). The research has used the analytical and descriptive method. The examined sample has involved (78) kindergarten teachers in the district of Lattakia. Results have showed that the level of Functional Performance of the Kindergarten Principals has been at a middle degree. The results have also showed significant and substantial differences in their performance level according to the teaching level in favor of the higher teaching level. The results have discovered significant variations according to the experience variable for the kindergarten principals with the higher experience. Results have indicated that the principals who had undergone training course have got a higher performance than those who had not. The researcher has presented suggestions for the improvement of the level of functional performance of the kindergarten principles. The most important suggestions are: an increase in the number of training courses of the kindergarten Principles, setting scientific bases for selecting the kindergarten principals with experiences and qualifications.